Predictive factors for endoscopic recurrence after ileocolic resection for Crohn’s disease - Akpınar, Hale (Turkish Journal of Gastroenterology, 2017)
Abstract Cite this article as: Akpınar H. Predictive factors for endoscopic recurrence after ileocolic resection for Crohn’s disease. Turk J Gastroenterol 2017; 28: 241-2.